A Model for the Simulation of Turbulent Boundary Layers in an Incompressible Stratified Flow - Slinn, Donald N.; Riley, J.J. (Journal of computational physics, 1998)
A model with several original physical and numerical features has been developed for direct numerical and large eddy simulations of a turbulent boundary layer in a stratified fluid. The large scale flow for which the model was developed involves internal waves reflecting from a sloping boundary. In the model, the internal waves are generated by a new technique that forces monochromatic waves at specified wavelengths and frequencies. A new analytic solution has been obtained representative of the forcing conditions. In the model, time discretization is based upon the projection method incorporating a third-order Adams–Bashforth scheme with variable time steps, and spatial discretization employs fourth-order compact differencing techniques on a variable grid that increases resolution close to the boundary. The model is periodic in two dimensions and in the third dimension employs an open boundary and a solid sloping surface. The pressure field is determined using a fast direct solution method of fourth-order accuracy. The model includes flow analysis aids such as tracking Lagrangian particles and advected scalar quantities. Flow measurements are made of the integrated kinetic and potential energy balances, local dissipation rates, and the energy spectra. The utility of the model is examined in a number of test problems. It appears that the model is well suited for simulations of transitioning and turbulent boundary layers.